LACUNA STRATIGRAFICA TRA LE FORMAZIONI DI RANZANO E DI ANTOGNOLA NELLE ZONE DI ROTEGLIA E MONTEBARANZONE (APPENNINO REGGIANO E MODENESE) (Rivista italiana di Paleontologia e Stratigrafia, 2020)
The Monte Piano — Blsmantova sequence (Middle Eocene — Late Miocene) in the Northern Apenmnes represents a new sedimentary cycle after the tectonic phase of the Early—Middle Eocene. This phase principally affected the structural Units of Ligurian domain. This sedimentary sequence (the postorogenic Ligurian Sequence), shows evidence of the progression of the Apennine orogenesis mainly through the development of unconformities of regional extension. In fact, this new sedimentary cycle began after the definitive closure of the Ligurian ocean (Oceanic stage) and sedimentation continued durIng the subsequent development of a collisional margin (Ensialic stage) between the European and African Adriatic plates.The stratigraphic and structural features of the Apenmne margin between Tresinaro Valley and Lavino Valley are described brteflv in this paper. Moreover, the contact between the Ranzano Formation and the Antognola Formation, parts of the postorogenic Ligurian Sequence, is discussed in terms of the micropaleontologica] data obtained from three stratigraphical sections situated In the lower valley of the Secchia River. The contact coincides with an unconformity that is marked by a biostratigraphical hiatus.In fact, foraminifera] associations indicate that the top of the Ranzano Formation is attributable to Zone PI 8 (Lower Oligocene) and that the base of the Antognola Formation is already attributable to Zone P 21 (Upper Oligocene). There was no evidence of the presence of Zone PI 9/20. The chronological range of the hiatus is estimated as 2.4 to 1 0 Ma, depending upon the chronological scale adopted and the exact position of the "top" of the Ranzano Formation and the base of the Antognola Formation.On the basis of the stratigraphic relations existing among the various units of the postorogenic Ligurian Sequence outcropping in the studied area and on the basis of the data collected on the contact between the Ranzano Formation and Antognola Formation, it is clear that the hiatus is attributable to submarine erosion of a part of the turbiditic deposits of the Ranzano Formation, which are affected by pronounced tectono—sedimentary phenomena. The tectonic movements developed in the Ligurian domain in a per10d preceding the deposition of the Antognola Formation. They are thus contemporary with the beginning of the deposition of the Macigno in the Tuscan paleogeographical domain.